CORRELATION STUDY OF SERUM CALCIUM LEVELS AND SERUM CARTILAGE OLIGOMERIC MATRIX PROTEIN LEVELS IN RHEUMATOID ARTHRITIS PATIENTS IN BANDUNG, INDONESIA - Saptarini, Nyi Mekar; Wibowo, Marlia Singgih; Gusdinar, Tutus (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was designed is to determine the correlation between serum calcium level and serum cartilage oligomeric matrix protein (COMP) level in Indonesian patients with rheumatoid arthritis (RA). Subjects and Methods: The subjects are patients who visit the rheumatology clinic at a government hospital in Bandung, Indonesia. Serum calcium level was determined by a complexometric method, and the serum COMP level was determined by enzyme-linked immunosorbent assay. Statistical analysis was performed with R software. Results: The serum calcium level was 82.24±44.82 mg/mL in RA patients and 99.04±60.56 mg/mL in normal controls. The serum COMP level was 843.80±35.79 ng/ml in RA patients and 830.00±48.92 ng/ml in normal controls. Conclusion: There is no correlation between serum calcium level and serum COMP levels in RA patients (p=0.967 and rho=0.006).